PROPUESTA DE TURISMO DE AVENTURA: EXCURSIONISMO EN LA RESERVA NATURAL PISACA, BARRIO SAN ISIDRO, CIUDAD DE CATACOCHA, CANTÓN PALTAS, PROVINCIA DE LOJA - Romero Robles, Soraya Maribel (2018)
Ecuador, being a mega diverse country, offers tourist products based on ecotourism and nature tourism, which are first and foremost nationally as the most commercialized, according to the Comprehensive Tourism Marketing Plan of Ecuador (2014). Adventure tourism has been incorporated in Ecuador in order to take advantage of its natural riches, as well as to make known to the world the diversity of places that invite the traveler to discover and explore the unexpected. The city of Catacocha cantonal capital of Paltas, is one of the 16 cantons of the province of Loja, has the Pisaca Natural Reserve which is one of the most important areas for the conservation and supply of water resources for the inhabitants of the city, this reserve is property of the Nature and International Culture Foundation, under its administration the flora has been conserved and also within its operational programs is the reforestation of it.. For this reason, this research aims to develop a proposal of adventure tourism: hiking in the Pisaca Natural Reserve, San Isidro neighborhood, city of Catacocha, Paltas canton, Loja province, complementing with three specific objectives. The first one is oriented towards carrying out the Tourist diagnosis of the "Pisaca Natural Reserve" of the city of Catacocha; the second is the design of an adventure tourism proposal: hiking; and the third objective was to identify the environmental impacts produced by tourism activity in the Pisaca Natural Reserve. In the first objective, the methodology of the local tourist diagnosis of Ricaurte (2009), the SWOT matrix, inventory tabs of attractions of the Ministry of Tourism (2017) were used; and from direct observation techniques and interviews with key actors. In the second objective, the Global Positioning System (GPS) was used to determine the UTM coordinates; The loading capacity was also determined with the methodology of Cifuentes (1992), for the application of the signage was based on the tourist signage manual of Ecuador. In the third objective, the Leopold matrix was applied, to determine the importance and magnitude of the impacts that may be generated in the development of the project. The proposal will allow positioning the Pisaca Natural Reserve as a tourist destination mainly for the city of Catacocha, as well as contributing to the people of the surrounding sectors generate a greater awareness of tourism and know the intrinsic value they possess. The recommendations are addressed to the Nature and International Culture Foundation and the Autonomous Decentralized Government of the Paltas Canton as actors involved in the management of the reserve.